Prediction of swimming competitive performance through lactate testing procedures - Gomes-Pereira, J.; Alves, F. (Medicine & Science in Sports & Exercise, 1998)
The relationship between blood lactate concentration and swimming competitive performance was evaluated. Swimming times were taken from competitions. Blood lactates were measured after a progressive lactate swimming test (based on each individual's race distance and technique) 48 hours after competing. There was no significant correlation between blood lactate in the test and competitive performance. It was concluded that blood lactate evaluations through a testing protocol have no relationship to competitive swimming performances and as such, are meaningless for predicting competitive performances. There was a suggestion that any value in lactate testing during training would be only associated with aerobic adaptation. Implication. Lactate testing in swimmers is generally a waste of time. Performance times are more likely to hold greater predictive and diagnostic values about training responses and impending competitive performances. Lactate values have only a weak relationship with aerobic training responses.